2013
DOI: 10.1016/s2214-1235(15)30142-3
|View full text |Cite
|
Sign up to set email alerts
|

In-hospital Outcomes of Patients with Cardiogenic Shock due to ST-Segment Elevation Myocardial Infarction

Abstract: Background: Cardiogenic shock is a clinical condition of inadequate tissue perfusion due to cardiac dysfunction. The most common etiology is ST-segment elevation myocardial infarction (STEMI) leading to left ventricular failure, but it may also be caused by mechanical complications such as acute mitral regurgitation, ventricular septal rupture or rupture of the left ventricular free wall. Despite therapeutic advances, mortality rates remain high. Methods: Retrospective, observational, single-center study, incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The results of our study showed a high intra-hospital mortality in the patients with acute myocardial infarction complicated by cardiogenic shock (62.6%), despite the use of primary percutaneous coronary intervention, which are significantly higher than the results of other randomized studies and registers where the intra-hospital mortality rate was 42%-48% [5][6][7][8][9] .…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…The results of our study showed a high intra-hospital mortality in the patients with acute myocardial infarction complicated by cardiogenic shock (62.6%), despite the use of primary percutaneous coronary intervention, which are significantly higher than the results of other randomized studies and registers where the intra-hospital mortality rate was 42%-48% [5][6][7][8][9] .…”
Section: Discussionmentioning
confidence: 77%
“…Despite the significant therapeutic progress, primarily in the sense of early myocardial revascularization strategy and aggressive inotropic and vasopressor support, cardiogenic shock continues to be the leading cause of death in acute myocardial infarction with the mortality rate of 42%-48% [5][6][7][8][9] .…”
Section: Introductionmentioning
confidence: 99%